Capacidade Aeróbica e Nível de Atividade Física em Idosos de Diferentes Faixas Etárias - Camila Camargos Zampa (2009)
Reference values for the aerobic capacity specifically to elderly people are rare and essential for the identification of functional impairment. Objectives: Characterize the aerobic capacity and the physical activity level of elderly people with different ages and establish reference equations for the oxygen uptake (VO2). Materials and Methods: The aerobic capacity of 63 community elderly people divided in group 1: 65-69, group 2 :70-79 and group 3: 80 and more years old was evaluated by incremental test with gas analysis using treadmill and ramp protocol and the physical activity level was identified by Human Activity Profile (HAP). Statistical analysis considering = .05 was carried out by non-parametric tests. Results: Median values of VO2 (21.8; 19.1; 16.6 mL.Kg-1.min-1) and carbon dioxide production (VCO2) (1755, 1367 and 1166 mL.min-1) decreased respectively in the groups 1, 2 and 3 with statistical significance between the groups 1 and 3. Correlations (p<0.001) were found between age and VO2 (r=-0.518), age and VCO2 (r=-0.549) and HAP and VO2 (r=0.498). The equations established by linear regression considering the time of incremental test (T) were: for men, VO2= 56.896 - (0.396 x Age) - (0.380 x BMI) + (0.410 x T) and for women, VO2= 44.954 - (0.394 x Age) - (0.178 x BMI) + (0.741 x T). Conclusions: This study confirms the gradual reduction of the aerobic capacity in elderly people and its relation with the age and with the physical activity level. The equations proposed may be used as reference for tests performed in elderly people according to the same protocol.